Forecasting Stok Sparepart Sepeda Motor Menggunakan Metode Double Exponential Smoothing(DES) - Gusrina Surianingsih; Havid Syafwan; Andy Sapta (STMIK Budi Darma, 2022)
PT. Anugerah Karya Abiwara II is a company engaged in the service sector in the workshop that serves its customers. The problem that occurs is the difficulty of determining the goods and the number of goods that must be provided every month in order to continue to meet customer needs. Stock or inventory is a number of goods provided by the company to meet consumer demand. Without adequate inventory, a business will not run smoothly. Therefore, to be more efficient, the authors designed a forecasting system with the Double Exponential Smoothing method using Visual Basic 2010 programming and MySQL database. The data predicted for the past 1 year are April 2021-March 2022 and the data will be forecasted in April. By calculating the Double Exponential Smoothing, the MAD value is 46.65, MSE 3975.26, RMSE 63.05, and the MAPE value is 21.48%, which means that the forecasting accuracy is almost 80%. So the algorithm with the DES method can be applied to the spare part stock forecasting process making it easier to determine the spare part stock in the next period.